1996
DOI: 10.1097/00006842-199605000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Social Fear

Abstract: The aims of the two studies were to investigate the relationship between emotions and immune responses in an experimental setting by inducing social fear and to broaden our understanding of bodily reactions by examining both cardiovascular and hormonal responses. Seventy-nine healthy subjects were confronted with a situation in which relatively strong social fear was induced in the laboratory. Social fear was induced by having to prepare and give an oral presentation in front of an audience. Thirty additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…These results confirm previous observations using public speaking or mental stress [18, 26] as stress models and similar patterns of change are also seen after intense emotional stress [10]. Recently it has been demonstrated that catecholamines play a determining role in stress-induced increases of NK cell numbers [12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results confirm previous observations using public speaking or mental stress [18, 26] as stress models and similar patterns of change are also seen after intense emotional stress [10]. Recently it has been demonstrated that catecholamines play a determining role in stress-induced increases of NK cell numbers [12].…”
Section: Discussionsupporting
confidence: 90%
“…Acute psychological stress was induced by public speaking and mental arithmetic [18]. Subjects were instructed to prepare a speech (topic: ‘Children’s position in today’s society’).…”
Section: Methodsmentioning
confidence: 99%
“…Situational procedures target social fear or physical fear. Social fear inductions include anticipated failure at an easy task or preparing a speech to be performed and evaluated by others (Gerritsen, Weigant, Bermond, & Frijda, 1996;Pauls & Stemmler, 2003;Schofield et al, 2017). Examples of paradigms that target physical fear include anticipated electric shock, abseiling down the side of a building, or interrogating participants after forcing them to commit a pseudocrime (e.g., Brooke & Long, 1987).…”
Section: Situational Proceduresmentioning
confidence: 99%
“…Both social and physical fear inductions are effective at increasing feelings of fear (e.g., Castaneda & Segerstrom, 2004). Additionally, situational procedures increased heart rate, skin conductance response, blood pressure, and decreased metabolic function (e.g., Gerritsen et al, 1996). These autonomic effects occur in comparison to both neutral controls and other emotions (e.g., anger; Pauls & Stemmler, 2003).…”
Section: Situational Proceduresmentioning
confidence: 99%
“…Speech stress in healthy men was found to result in significant increases in Ts cells and NK cells and a reduction in the Th/Ts ratio versus baseline (25). Gerritsen and colleagues (26) also found that a laboratory induced fear situation (public speaking) produced changes in the experimental subjects' immune systems, and specifically reduced the numbers of Th cells and T lymphocytes. Heightened stress as well as heritable factors has been suggested to contribute to the onset of panic disorder (27).…”
Section: Discussionmentioning
confidence: 99%